Geopolitics of Energy - Muskaj, Blerina (European Journal of Multidisciplinary Studies, 2016)
At the beginning of my paper I will explain the concept of "Geopolitics of Energy", this will be done for a quite simple reason, because I want everyone who can sit to read this article to understand more clearly what is at stake, therefore allow them the comprehension of what is being elaborated bellow at first sight. Geopolitics of energy is a concept that relates to policies choosing exporters to implement on importers, is the policy that has an impact on energy consumption, which includes consumer’s choice in the geopolitical context, taking into account the economy, foreign policy, the safety of energy, environmental consequences and priorities that carries the energy exporter. This concept permits the understanding of how works the politics that undertakes this initiative taking into account natural resources such as: natural gas and oil. Natural gas and oil are two main resources that produce energy but also two main elements on which arises all the topic in the energetics game. For this paper is used qualitative methodology, through which we were able to accomplish this work. I focused on scientific literature, official publications and reports on energy geopolitics. The main aim has been to show how in this decade, energy security is at the center of geopolitical agenda and has become the focus of numerous political debates. Regarding this point of view, Europe is taking the initiative to create a common energy market within the continent by creating projects, in which Albania appears as a new regional energy potential. Russia, which is aiming to play a role in the international arena, is seeking to position itself geopolitically in "its political weapon", hydrocarbon resources, in particular natural gas resources.
Keywords: geopolitics,energy,resources,